O aspecto verbal em Apolodoro: um estudo baseado em corpus sobre os padrões de usos aspectuais em Biblioteca - Trindade, Alexandre Wesley [UNESP] (2012)
The aim of this work was to analize the patterns of aspect usages in Greek writer Apollodorus, by means of empirical approach, from a electronic database and statistically tested. The main methodological underpinning for the exploratory research was provided by Corpus Linguistics because in the fundamental concept language is a probabilistic system and it must be studied by an empirical approach. The assumption of this view of language is that the theoretical possibilities of linguistic features do not correspond with the frequency of occurrence. This difference is not significant only in statistical point of view, it demonstrates that is typical of language the presence of (i) a regular pattern showed and (ii) a systematic variations. As language patterns were considered collocational patterns. The corpus chose was the work Library (Biblioteca in portuguese), whose authorship is attributed to Apollodorus, first century CE. This corpus is therefore suitable for the study of patterns of aspect usages because it is composed of authentic texts in natural language. The identification of verbal aspect was due to the ending location of the pertinent verbal correlate with higher rate of frequency, using the program AntConc, which generated a word list listing the verbs accounted for. From the occurrences of verbs chosen was established the most frequent verbal aspect in order to define the unit of analysis. The selection criterion was given verbal aspects of the opposition of verbal stems, considering the opposition of three verbal stems: present stem, perfect stem, and aorist stem. The corpus used in the AntConc program was not tagged. In order to examine, POS tagging was used to steady in the Perseus Digital Library. Among the sample of verbal occurrences, the stem of the aorist had the highest frequency. Through statistical analysis, collocational pattern infinitive + participle was the most frequent